GROWTH RATES OF ISLAMIC FINANCE: A BIBLIOMETRIC ANALYSIS BASED ON THE NUMBER OF PUBLICATIONS - Nur Iza Faizah; Fidri Fadillah Puspita; Diana Lestari; Indriyeni Indriyeni (IAIN Batusangkar, 2021)
Islamic Finance, which is related to